Proper Use of Capillary Number in Chemical Flooding. (1st March 2017) - Guo, Hu; Dou, Ma; Hanqing, Wang; Wang, Fuyong; Yuanyuan, Gu; Yu, Zhaoyan; Yansheng, Wang; Li, Yiqiang
Abstract : Capillary number theory is very important for chemical flooding enhanced oil recovery. The difference between microscopic capillary number and the microscopic one is easy to confuse. After decades of development, great progress has been made in capillary number theory and it has important but sometimes incorrect application in EOR. The capillary number theory was based on capillary tube bundles and Darcy's law hypothesis, and this should always be kept in mind when used in chemical flooding EOR. The flow in low permeability porous media often shows obvious non-Darcy effects, which is beyond Darcy's law. Experiments data from ASP flooding and SP flooding showed that remaining oil saturation was not always decreasing as capillary number kept on increasing. Relative permeability was proved function of capillary number; its rate dependence was affected by capillary end effects. The mobility control should be given priority rather than lowering IFT. The displacement efficiency was not increased as displacement velocity increased as expected in heavy oil chemical flooding. Largest capillary number does not always make highest recovery in chemical flooding in heterogeneous reservoir. Misuse of CDC in EOR included the ignorance of mobility ratio, Darcy linear flow hypothesis, difference between microscopic capillary number and the microscopic one, and heterogeneity caused flow regime alteration. Displacement of continuous oil or remobilization of discontinuous oil was quite different.